One wish - Carr, Robyn (Don Mills, Ontario : MIRA Books, 2015)
Starting a new life as a flower-shop owner, former champion figure skater Grace Dillon begins a no-strings- attached relationship with high school teacher Troy Headly, and when Grace's past comes back to haunt her, Troy doubles down on their relationship and brings it to the next level.
Keywords: Florists -- Fiction; Women figure skaters -- Fiction; Interpersonal attraction -- Fiction; High school teachers -- Fiction; Oregon -- Fiction; Love stories